Is starvation a cause of overmortality of the Mediterranean sardine?. (August 2021) - Queiros, Quentin; Saraux, Claire; Dutto, Gilbert; Gasset, Eric; Marguerite, Amandine; Brosset, Pablo; Fromentin, Jean-Marc; McKenzie, David J.
Abstract: Animal mortality is difficult to observe in marine systems, preventing a mechanistic understanding of major drivers of fish population dynamics. In particular, starvation is known to be a major cause of mortality at larval stages, but adult mortality is often unknown. In this study, we used a laboratory food-deprivation experiment, on wild caught sardine Sardina pilchardus from the Gulf of Lions. This population is interesting because mean individual phenotype shifted around 2008, becoming dominated by small, young individuals in poor body condition, a phenomenon that may result from declines in energy availability. Continuous monitoring of body mass loss and metabolic rate in 78 captive food-deprived individuals revealed that sardines could survive for up to 57 days on body reserves. Sardines submitted to long-term caloric restriction prior to food-deprivation displayed adaptive phenotypic plasticity, reducing metabolic energy expenditure and enduring starvation for longer than sardines that had not been calorie-restricted. Overall, entry into critical fasting phase 3 occurred at a body condition of 0.72. Such a degree of leanness has rarely been observed over 34 years of wild population monitoring. Still, the proportion of sardines below this threshold has doubled since 2008 and is maximal in January and February (the peak of the reproductive season), now reaching almost 10 % of the population at that time. These results indicate that the demographic changes observed in the wild may result in part from starvation-related adult mortality at the end of the winter reproductive period, despite adaptive plastic responses. Highlights: Laboratory fasting experiment informs about natural mortality in the wild. Sardines reduce their metabolic energy expenditures to endure long fasting. Calorie-restricted sardines display better phenotypic plasticity to face fasting. Entry into critical fasting phase 3 occurred at a body condition of 0.72 Sardines in critical condition represent now 10 % of the population in the wild.